2016
DOI: 10.1002/etc.3673
|View full text |Cite
|
Sign up to set email alerts
|

Passage of fiproles and imidacloprid from urban pest control uses through wastewater treatment plants in northern California, USA

Abstract: Urban pest control insecticides-specifically fipronil and its 4 major degradates (fipronil sulfone, sulfide, desulfinyl, and amide), as well as imidacloprid-were monitored during drought conditions in 8 San Francisco Bay (San Francisco, CA, USA) wastewater treatment plants (WWTPs). In influent and effluent, ubiquitous detections were obtained in units of ng/L for fipronil (13-88 ng/L), fipronil sulfone (1-28 ng/L), fipronil sulfide (1-5 ng/L), and imidacloprid (58-306 ng/L). Partitioning was also investigated;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 37 publications
3
62
1
Order By: Relevance
“…They include many pharmaceuticals, pesticides, and industrial chemicals with potent ecotoxicological effects (de Brito Rodrigues et al 2017;Parolini et al 2017;Thorngren et al 2017;Villeneuve et al 2017;Young et al 2017). Aquatic organisms are particularly vulnerable to their presence because a number of PIOCs are detected in different water bodies and can persist through harsh treatment processes (Maruya et al 2016;Cantwell et al 2017;Sadaria et al 2017). Because amphipods occupy important ecological roles in aquatic ecosystems, further refinement of the current amphipod BCF model will facilitate the integrated risk assessment of PIOCs in aqueous environments, as prompted by increasing public understanding and legislative pressure (European Commission 2017).…”
Section: Discussionmentioning
confidence: 99%
“…They include many pharmaceuticals, pesticides, and industrial chemicals with potent ecotoxicological effects (de Brito Rodrigues et al 2017;Parolini et al 2017;Thorngren et al 2017;Villeneuve et al 2017;Young et al 2017). Aquatic organisms are particularly vulnerable to their presence because a number of PIOCs are detected in different water bodies and can persist through harsh treatment processes (Maruya et al 2016;Cantwell et al 2017;Sadaria et al 2017). Because amphipods occupy important ecological roles in aquatic ecosystems, further refinement of the current amphipod BCF model will facilitate the integrated risk assessment of PIOCs in aqueous environments, as prompted by increasing public understanding and legislative pressure (European Commission 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Its ingestion by animals can produce pre‐eminently hepatotoxicity, along with immunotoxic, nephrotoxic, and oxidative stress effects . Imidacloprid is highly resistant to degradation and, consequently, it has been detected at concentrations up to 52 μg L −1 in agricultural water and 0.36 μg L −1 in urban wastewater . The destruction of this pollutant was feasible using ultrasounds combined with UV radiation and H 2 O 2 , as well as EAOPs like EO, and EF .…”
Section: Introductionmentioning
confidence: 94%
“…In another study, fipronil and its derivatives were found in the WWTP influent at 1-88 ng/L, 62% in the water phase, with the remainder being bound to filter-removable particulates. Total fiproles persisted during the treatment, with 65 ± 11% remaining in water and the balance partitioning into sludge, with fipronil at 3.7-151 ppb dry weight (Sadaria et al 2017). The authors identified imidacloprid, acetamiprid, clothianidin, and fiproles as recalcitrant sewage constituents that persist through WWTPs.…”
Section: Watermentioning
confidence: 99%